Strategic Collaborations and Diversification: Pathways to Sustainable Growth in Bali’s Tourism Village and Business Ecosystems - Ni Made Ary Widiastini; I Ketut Sida Arsa; Made Aristia Prayudi; Ni Luh Putu Agustini Karta (Universitas Udayana, 2025)
Tourism villages contribute significantly to Bali's economic development by promoting rural entrepreneurship. However, the sector faces challenges such as low product quality, ineffective marketing, and competition from low-cost imported products. This study explores collaboration and diversification strategies to ensure the economic sustainability of Bali’s village tourism and rural businesses. Data were collected through observations, questionnaires, and in-depth interviews, then analyzed using the SWOT method to assess strengths, weaknesses, opportunities, and threats. The results highlight the importance of community involvement, partnership networks, creative product development, effective marketing, and long-term business management. Findings from four villages indicate that collaboration with local industries and sustainable tourism initiatives enhances community income. To support sustainable tourism and improve community welfare, it is recommended that the government and stakeholders strengthen the promotion of local products and maximize the cultural and economic potential of villages.